3(x-2)=-26-7x

Simple and best practice solution for 3(x-2)=-26-7x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-2)=-26-7x equation:


Simplifying
3(x + -2) = -26 + -7x

Reorder the terms:
3(-2 + x) = -26 + -7x
(-2 * 3 + x * 3) = -26 + -7x
(-6 + 3x) = -26 + -7x

Solving
-6 + 3x = -26 + -7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7x' to each side of the equation.
-6 + 3x + 7x = -26 + -7x + 7x

Combine like terms: 3x + 7x = 10x
-6 + 10x = -26 + -7x + 7x

Combine like terms: -7x + 7x = 0
-6 + 10x = -26 + 0
-6 + 10x = -26

Add '6' to each side of the equation.
-6 + 6 + 10x = -26 + 6

Combine like terms: -6 + 6 = 0
0 + 10x = -26 + 6
10x = -26 + 6

Combine like terms: -26 + 6 = -20
10x = -20

Divide each side by '10'.
x = -2

Simplifying
x = -2

See similar equations:

| 7z-1=2(4z-3) | | (x+64)=(2x+39) | | 40+5x=5(7+2x) | | 3/4x-9=7 | | (3/2)x-163x | | -23=-9f-4f | | 2x+4y+2-y-9x-5= | | 4.75t+5=13.5t+12 | | Y=cos(5*x)+sin(5*x) | | 3m-4n-7=8m+n-6 | | 24-8x=-2(4x+10) | | 3y+-5=5y | | 90+(3x-1)+31=180 | | 4.19/4 | | 7(5x-3)=10 | | 2x(100/45):3x(100/36) | | 9h-3-6h=16 | | 2(3x+6)+3(3x-4)= | | 0.06/1=x/30 | | 3z-4z=-30 | | 2+5=x-7 | | 4x-5(6x-6)=2-7(x-5) | | 1.14/1=x/30 | | 8-z=-22 | | 16/54 | | 4v-7v=-21 | | -20=7+9x | | 0.06/1=x/5 | | -7x+7=-5x+25 | | 0=4x^2+2x+32 | | K/-8.8=-12.9 | | (x)(-7)=42 |

Equations solver categories